2010
DOI: 10.1080/12538078.2010.10516184
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Tunisian accessions ofAegilops geniculataRoth and durum wheats (Triticum durumDesf.) using RAPD markers

Abstract: Abstract.-Genetic diversity of three durum wheat cultivars (Triticum durumDesf.) and thirteen Aegilops geniculata Roth accessions belonging to different regions of Tunisia (in North and Central) was evaluated using random amplified polymorphic DNA (RAPD) markers. Nineteen arbitrary universal primers were used for the amplification of random DNA sequences. Data were analysed with the SIMQUAL program using the NTSYS-pc. Phylogenetic diagram was drowning using the UPGMA algorithm. Results indicate an important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, other molecular approaches have been developed to obtain better knowledge of the phenomena of speciation and evolution in these species, e.g. the study of reserve proteins (Fernández-Calvín and Orellana 1990;Rodriguez-Quijano et al 2000;Sun et al 2006) and DNA polymorphism (Zhang et al 1996;Zaharieva et al 2001;Sasanuma et al 2004;Salina et al 2006;Haider and Nabulsi 2008;Mahjoub et al 2010;Giraldo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, other molecular approaches have been developed to obtain better knowledge of the phenomena of speciation and evolution in these species, e.g. the study of reserve proteins (Fernández-Calvín and Orellana 1990;Rodriguez-Quijano et al 2000;Sun et al 2006) and DNA polymorphism (Zhang et al 1996;Zaharieva et al 2001;Sasanuma et al 2004;Salina et al 2006;Haider and Nabulsi 2008;Mahjoub et al 2010;Giraldo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found that in the majority of polyploid Aegilops species, the genome is variously modified as compared to their ancestors. However, other molecular approaches have been developed, such as the study of reserved proteins (Fernandez-Calvin, Orellana, 1990;Rodriguez-Quijano et al, 2000;Sun et al, 2006) and DNA polymorphism (Zhang et al, 1996;Zaharieva et al, 2001;Sasanuma et al, 2004;Salina et al, 2006;Haider et al, 2008;Mahjoub et al, 2010;Giraldo et al, 2016) for better knowledge of speciation processes and genomic evolution in these species.…”
Section: Introductionmentioning
confidence: 99%
“…They found that in the majority of polyploid Aegilops species, the genome is variously modified as compared to their ancestors. However, other molecular approaches have been developed, such as the study of reserved proteins (Fernandez-Calvin, Orellana, 1990;Rodriguez-Quijano et al, 2000;Sun et al, 2006) and DNA polymorphism (Zhang et al, 1996;Zaharieva et al, 2001;Sasanuma et al, 2004;Salina et al, 2006;Haider et al, 2008;Mahjoub et al, 2010;Giraldo et al, 2016) for better knowledge of speciation processes and genomic evolution in these species.…”
Section: Introductionmentioning
confidence: 99%